2016
DOI: 10.1161/circulationaha.116.024014
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Ticagrelor on Myocardial Injury After Infarction

Abstract: Ticagrelor, beyond its antiplatelet efficacy, exerts cardioprotective effects by reducing necrotic injury and edema formation via adenosine-dependent mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
81
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(90 citation statements)
references
References 50 publications
6
81
1
Order By: Relevance
“…Recent reports suggest that ticagrelor may provide additional protection over that from clopidogrel because of its ability to increase tissue adenosine levels, 16,17 and ticagrelor is now widely used before recanalization interventions. We used cangrelor in the present study because an intravenous drug simplifies the protocol.…”
Section: Resultsmentioning
confidence: 99%
“…Recent reports suggest that ticagrelor may provide additional protection over that from clopidogrel because of its ability to increase tissue adenosine levels, 16,17 and ticagrelor is now widely used before recanalization interventions. We used cangrelor in the present study because an intravenous drug simplifies the protocol.…”
Section: Resultsmentioning
confidence: 99%
“…This is of potential interest as there is evidence for adenosineinduced protection against ischemia-reperfusion injury 139,140 . In fact, ticagrelor has been shown to confer cardioprotection in animal studies of ischemia-reperfusion in an adenosinedependent manner [141][142][143][144] . Whether ticagrelor protects against ischemia-reperfusion injury in humans has not been investigated previously.…”
Section: Ticagrelormentioning
confidence: 99%
“…In the PLATO-trial, ticagrelor was associated with better cardiovascular outcomes and survival compared to clopidogrel 134 . The precise underlying mechanism for this superiority of ticagrelor has not been confirmed, but studies in rats 141,142 , pigs 143 and dogs 193 have shown that despite a similar degree of platelet inhibition, treatment with ticagrelor reduces infarct size after myocardial ischemiareperfusion to a greater extent than treatment with clopidogrel, indicating a pleiotropic cardioprotective effect. Apart from being a P2Y12 receptor blocker, ticagrelor also increases extracellular adenosine levels through inhibition of the equilibrative nucleoside transporter 1 (ENT1) 137 , leading to impeded uptake of adenosine in erythrocytes.…”
Section: Effect Of Ticagrelor Treatment On the Endotheliummentioning
confidence: 99%
“…In particular, preventing adenosine cellular uptake effectively extends the half-life of adenosine increasing extracellular levels of locally produced endogenous adenosine. This action has been supposed important in condition of hypoxia, where increased adenosine levels may contribute to vasodilatation, ischemic preconditioning, and inhibition of inflammatory response [27]. Moreover, this adenosine-mediated secondary mode of action of ticagrelor may provide a plausible mechanistic explanation of the cardioprotective effects, observed in the PLATO study [9].…”
Section: Discussionmentioning
confidence: 85%